2023
DOI: 10.1038/s41598-023-40379-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive examination of tattoo removal using a 150 ps Nd:YAG laser in a porcine model

Abstract: This study aimed to investigate the efficacy of a Nd:YAG laser with a pulse duration of 150 ps at different laser parameters. The effects on multiple-colored tattoos with such ultrashort pulses has not been previously described in the literature. In vivo experiments were conducted on porcine skin to analyze the fragmentation efficiency of five different tattoo colors using different wavelengths, pulse energies, and spot sizes. The results showed that the optimal tattoo clearance to safety ratio for blue, green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Mononuclear cells, which include macrophages and lymphocytes, play a pivotal role in the immune response to tissue injury [5]. Their infiltration indicates an active immune response to the laser-induced thermal damage, which is crucial in clearing the fragmented tattoo pigments [6]. Interestingly, it was also observed that the severity of this mononuclear cell infiltration was directly influenced by the quantity of pigment deposits in the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mononuclear cells, which include macrophages and lymphocytes, play a pivotal role in the immune response to tissue injury [5]. Their infiltration indicates an active immune response to the laser-induced thermal damage, which is crucial in clearing the fragmented tattoo pigments [6]. Interestingly, it was also observed that the severity of this mononuclear cell infiltration was directly influenced by the quantity of pigment deposits in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these challenges, ongoing research investigates novel approaches to enhance colored tattoo clearance. This includes exploring new laser wavelengths, combination therapies with beam-splitting optics [5], and pulse durations, as demonstrated in our previous study using a 150 ps Nd: YAG laser for treating multicolored tattoos in a porcine model [6].…”
Section: Introductionmentioning
confidence: 99%